Cognitive Restructuring Techniques in Increasing Self-Confidence of Body Shaming Victims Shaming Student of SMK N 8 Pontianak: - - Aini, Nur; Lestari, Desi Puji; Rahmi, Hesty Nur (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2024)
Body shaming is a phenomenon that many women experience because they do not meet beauty standards. The purpose of this study is to describe the form, impact, assertive behavior of female students against body shaming and cognitive restructuring techniques in an effort to increase the victim's self-confidence. the method in this study uses a qualitative approach of case study type, the instruments used are semi-structured interviews and observation. Purposive sampling as a sampling technique. The location of this research was at SMK N 8 Pontianak. The results of the study found that most students experienced fat shaming, skinny shaming, skin color shape. Body shaming has the impact of loss of self-confidence in individuals. Students showed that they did not have assertive behavior, therefore researchers used cognitive restructuring techniques to increase individual self-confidence and assertiveness training to increase the assertive behavior of the sample, because assertive behavior is needed to reduce the occurrence of body shaming.